In vitro anti-gastrointestinal cancer activity of Toxocara canis-derived peptide: Analyzing the expression level of factors related to cell proliferation and tumor growth - Bahadory, Saeed; Sadraei, Javid; Zibaei, Mohammad; Pirestani, Majid; Dalimi, Abdolhossein (Frontiers in Pharmacology, 2022)
Background: Recently, a hypothesis about the negative relationship between cancers and parasites has been proposed and investigated; some parasitic worms and their products can affect the cancer cells proliferations. Due to the potential anti-cancer effect of helminthic parasites, in the present study, the excretory-secretory protein of Toxocara canis (T.canis) parasite was used to evaluate the possible anti-cancer properties and its effect in gastrointestinal and liver cancer cells proliferations related genes in laboratory conditions. Methods and material: The selected synthesized peptide fraction from T.canis excretory-secretory Troponin protein peptide (ES TPP) was exposed at 32, 64, 128 and 256 μg/ml concentrations to three gastrointestinal cancer cell lines AGS, HT-29 and Caco 2, as well as HDF cells as normal cell lines. We used MTT assay to evaluate cellular changes and cell viability (CV). Variations in genes (Bcl-2, APAF1, ZEB1, VEGF, Cyclin-D1, and caspase-3) expression were analyzed using real-time RT-PCR. Result: After 24h of exposure to peptides and cell lines, a decrease in CV was observed at concentrations of 64μg/ml and compared to the control group. Next 48h, a significant decrease in the CV of Caco 2 cells was observed at concentrations of 32μg/ml; in the other cancer cell lines, concentrations above 32μg/ml were effective. The peptide was able to significantly alter the expression of the studied genes at a concentration of 100 μg/ml. Conclusion: Although the studied peptide at high concentrations could have a statistically significant effect on cancer cells, it is still far from the standard drug and can be optimized and promising in future studies.